2019
DOI: 10.1002/smll.201901427
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Dentin Phosphophoryn‐Derived Peptide‐Functionalized Lignin Nanoparticles for Enhanced Cellular Uptake

Abstract: The surface modification of nanoparticles (NPs) using different ligands is a common strategy to increase NP−cell interactions. Here, dentin phosphophoryn‐derived peptide (DSS) lignin nanoparticles (LNPs) are prepared and characterized, the cellular internalization of the DSS‐functionalized LNPs (LNPs‐DSS) into three different cancer cell lines is evaluated, and their efficacy with the widely used iRGD peptide is compared. It is shown that controlled extent of carboxylation of lignin improves the stability at p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 58 publications
0
56
0
Order By: Relevance
“…applications already proven for other forms of lignin, but where spherical particles could give an advantage. Focusing on the size and shape of the particles introduce totally novel lignin applications, including drug delivery [6][7][8][9][10][11] and enzyme immobilization 12,13 for biocatalysis.…”
Section: Monika öSterbergmentioning
confidence: 99%
See 1 more Smart Citation
“…applications already proven for other forms of lignin, but where spherical particles could give an advantage. Focusing on the size and shape of the particles introduce totally novel lignin applications, including drug delivery [6][7][8][9][10][11] and enzyme immobilization 12,13 for biocatalysis.…”
Section: Monika öSterbergmentioning
confidence: 99%
“…Figueiredo et al synthesized carboxylated kraft lignin using succinic anhydride and found that excessive succinylation rendered lignin water-soluble, while a lower extent of succinylation allowed for peptide grafting on LNPs in water. 8 Like for pH, the ionic strength of the dispersing media interferes with the stability of the kraft (LignoBoost) lignin particles. Lievonen et al showed a significant shift to less negative zeta potential of the lignin particles upon addition of NaCl (from −60 to −10 mV); however, the dispersion was still stable at 500 mM NaCl and the particle size remained unchanged after seven days.…”
Section: The Stability In Applications and Rate Of Degradation Of Ligmentioning
confidence: 99%
“…Figueiredo et al. systematically explored a variety of functionalized lignin nanoparticles with respect to their preparation, cytotoxicity, drug loading capacity, drug release behavior, and interaction with cells in vitro . They reported the preparation of three different lignin nanoparticles, namely, pure lignin nanoparticles (pLNPs), iron(III)‐complexed lignin nanoparticles (Fe‐LNPs), and magnetic Fe 3 O 4 ‐infused lignin nanoparticles (Fe 3 O 4 ‐LNPs), and evaluated their application potential as a nanomedicine from multiple perspectives.…”
Section: Drug and Gene Deliverymentioning
confidence: 99%
“…Generally, amino groups of DSS were chemically conjugated with carboxyl groups of LNPs by 1‐ethyl‐3‐(3‐dimethylaminopropyl)carbodiimide and N ‐hydroxysuccinimide (EDC/NHS) coupling chemistry in a mild buffer environment, which has no negative effect on loading efficiency. Owing to the effect on enhanced cellular internalization, the resultant BZL@LNPs–DSS nanosystem not only increased the dissolution rate and stability of BZL in a mimicked tumor microenvironment, but also had a very positive effect on enhancing the cellular internalization and antiproliferative effects in 2 D or 3 D tumor mode …”
Section: Drug and Gene Deliverymentioning
confidence: 99%
“…The DSS repeats are derived from a motif found in dentin phosphophoryn, one of nature's most acidic proteins, which was previously demonstrated by us to deliver quantum dots into live cells (21). Furthermore, the DSS motif was used to coat lignin nanoparticles, facilitating their efficacy as a drug delivery agent for several types of cancer cells (36). To enable stable single-particle imaging, QD-laden T cells were immobilized on activating surfaces.…”
Section: Introductionmentioning
confidence: 99%